First Among Equals: Christian Theology and Modern Philosophy. (July 2017) - Woods, Paul
Christian theology can and should interact with modern philosophical trends and ideas to remain relevant to contemporary society. The roots of critical engagement between theology and philosophy are ancient, going back to the nature of the Triune God and the Bible itself and his broad kingdom redemptive commission to the Church. Scripture is finite, anchored in space and time, but the truths within it can generate responses to new situations. Theology sits alongside other disciplines in a relationship of 'first among equals', benefitting from and critiquing human thought.